Designing Integrated Promotional Communication: IMC-Based Digital Assistance Initiative for MSMEs - Arfa, Daghastaniy Fairuzza; Hakim, M. Luqmanul; Rofiqoh, Yusnia I'anatur; Ahar, Sofia; Irfa’i, Afif Fadzillah; Itsnain, Firdausi Nurul (Universitas Muhammadiyah Sidoarjo, 2023)
The COVID-19 pandemic has had a significant impact on the sustainability of MSMEs in Indonesia, particularly in terms of direct product promotion and marketing. This training aims to equip MSME actors with the understanding and skills to strategically utilize digital media through an Integrated Marketing Communication (IMC) approach. The training was conducted online via Zoom Meetings using an interactive approach, including presentations, discussions, and question-and-answer sessions. The results of the activity demonstrated an increase in SME operators' understanding of integrated promotion strategies, the use of social media as a marketing communication tool, and the development of more creative and relevant promotional messages. This training is expected to serve as the first step in building the resilience of SMEs in the post-pandemic digital era.